Comparative Study of Physical Education Management in Sports-Based Schools and Regular Schools in Facing The Demands of The 2025 Curriculum - Galih Farhanto; Marki Sandi; Donny Setiawan (Sekolah Tinggi Olahraga & Kesehatan Bina Guna, 2025)
The implementation of the 2025 Curriculum brings significant changes to the educational paradigm, including in Physical Education (PE) subjects. This curriculum emphasizes the development of holistic competencies, which include cognitive, motor, and affective aspects. This study aims to compare the physical education management models between sports-based schools and regular schools in East Java Province in facing the demands of this new curriculum. This research uses a qualitative approach with a comparative case study method. The research subjects consisted of teachers, principals, and physical education coordinators from two selected Sports-based schools and two Regular schools. Data were collected through in-depth interviews, participatory observation, and document analysis. It was found that Sports-based schools have advantages in terms of time allocation, teacher qualifications, and facilities. However, Regular schools showed flexibility in integrating the curriculum with other subjects. Both types of schools faced different challenges in terms of evaluation and parental involvement. Sports-Based Schools were better prepared in terms of infrastructure and human resources, while Regular schools showed better adaptation in holistic pedagogical approaches.